Influence of antipsychotics on metabolic syndrome risk in patients with schizophrenia - Koricanac, Aleksandra; Tomic Lucic, Aleksandra; Veselinovic, Mirjana; Bazic Sretenovic, Danijela; Bucic, Gorica; Azanjac, Anja; Radmanovic, Olivera; Matovic, Mirjana; Stanojevic, Marijana; Jurisic Skevin, Aleksandra; Simovic Markovic, Bojana; Pantic, Jelena; et al. (Frontiers in Psychiatry, 2022)
Objective: Many studies so far have suggested an effect of antipsychotic therapy in patients diagnosed with schizophrenia in the development of metabolic syndrome. Our goal was to determine where the risk of metabolic disorder is higher and why. We used and considered all available measurements, indices and clinical assessment scales in respondents and searched for the correlation of IL-33, TGF-β and TNF-α within them. Methods: In a stable phase, 60 patients diagnosed with schizophrenia were equally divided into three groups according to the drug (risperidone, clozapine and aripiprazole monotherapy). Control group had 20 healthy subjects. The Positive and Negative Syndrome Scale (PANSS) was used.Prolactin, lipid status, glycaemia, insulin, cytokine values (IL-33, TGF-β and TNF-α) andC-reactive protein (CRP) were measured. Body mass index (BMI), Homeostatic Model Assesment for Insulin Resistance (HOMA index), waist and hip circumference (WHR) and blood pressure measurement were performed in the study. Results: Patients treated with risperidone had statistically higher values of prolactin. HDL cholesterol values were significantly lower in all three mentioned groups. Values of glucose were statistically higher in clozapine group, and BMI was statistically significantly higher in clozapine and aripiprazole group. In the risperidone and clozapine treated patients IL-33 showed statistically significant correlation with glucose, prolactin and BMI,than TGF β with triglycerides, insulin, HOMA index and WHR and TNF α with glucose, BMI and HOMA index. In the aripiprazole group none statistically significant correlation in cytokines was found. Conclusion: Patients on risperidone and clozapine therapy are at greater risk of developing metabolic syndrome than patients treated with aripiprazole. Decreased concentration of TGF β was statistically significant in the group of patients treated with risperidone.